1992
DOI: 10.1017/s0950268800049736
|View full text |Cite
|
Sign up to set email alerts
|

Each water outlet is a unique ecological niche forLegionella pneumophila

Abstract: SUMMARYWe determined the natural history of the colonization of our hospital's potable water by culturing water approximately biweekly from 20 sites throughout the hospital for 4 years. Overall, 545 (24-7 %) of the 2200 samples grew Legionella pneumophila. During hyperchlorination, 11 7 % of the samples were positive while 41P6 % were positive in the absence of chlorination. There was no seasonal trend towards positivity, but there was marked inter-site variation in the semiquantitative culture results. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
(13 reference statements)
0
13
1
1
Order By: Relevance
“…States et al (1989) showed the potential for Legionella growth within municipal systems, and this supports the hypothesis that public water supplies may contaminate the plumbing systems of hospitals and other large buildings. Individual water outlets in hospitals can each serve as its own ecological niche of L. pneumophila (Marrie et al, 1992). In a study of Legionella in the hot water distribution systems of Finnish apartment buildings, Zacheus and Martikainen (1994) found the highest concentrations of legionellae in the shower water.…”
Section: Environmental Sources Of Legionellosismentioning
confidence: 99%
“…States et al (1989) showed the potential for Legionella growth within municipal systems, and this supports the hypothesis that public water supplies may contaminate the plumbing systems of hospitals and other large buildings. Individual water outlets in hospitals can each serve as its own ecological niche of L. pneumophila (Marrie et al, 1992). In a study of Legionella in the hot water distribution systems of Finnish apartment buildings, Zacheus and Martikainen (1994) found the highest concentrations of legionellae in the shower water.…”
Section: Environmental Sources Of Legionellosismentioning
confidence: 99%
“…Water was cultured every 2 weeks for 4 years from 20 sites throughout the hospital. 14 Of the 2200 samples, 545 (24.7%) were positive for L. pneumophila serogroup 1. During periods of hyperchlorination, 11.7% of the samples were positive compared with 41.6% when the water was not being hyperchlorinated.…”
Section: Biology and Reservoirs Of Legionella Speciesmentioning
confidence: 99%
“…At hospital A, most of the isolates have contained one of the following plasmids: a 23-MDa plasmid (type II), 72-and 96-MDa plasmids (type III), and a 100-MDa plasmid (type VI). A few isolates had a 70-MDa plasmid (type IV), an 89-MDa plasmid (type V), and 58-and 103-MDa plasmids (type VII) (5). The potable water at both of these hospitals remained positive for Legionella from 1987 until the present for hospital A and until its demolition in 1996 for hospital B (where plasmidless isolates were obtained).…”
mentioning
confidence: 96%